PENGARUH PENYULUHAN DENGAN MEDIA ANIMASI KARTUN TERHADAP TINGKAT PENGETAHUAN TENTANG MENYIKAT GIGI PADA SISWA/I KELAS IV-B SD NEGERI 104219 TANJUNG ANOM KEC. PANCUR BATU - sondang, sondang; Saragih, Apri Yustika (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
One effort to elivate knowledge is health counseling. Counseling with various targets is more emphasized to groups of school children. The school environment is an extension of the family's hands in laying the foundation of healthy living behavior in school children. In addition, 40% -50% of the total population is at school children age, 6-12 years that health counseling efforts on school children's should be the foremost priority. Health counseling in schools is integrated into the school health program (UKS). This study aimed to determine the effect of counseling with cartoon animation media to the level of students’ knowledge about tooth brushing among the students of grade IV-B SD Negeri 104219 Tanjung Anom, Pancur Batu Subdistrict. The research used quasi experiment method with one group pre and post test while for the statistic test, t-test dependent test was used. The result of t-Test dependent test was p value = 0,00, because p <0,05 then Ho was rejected and Ha was accepted, meaning that this research showed that counseling with cartoon animation media had an effect to elevate knowledge about toothbrushing. It is expected that students expand their insight and knowledge about how to brush the teeth properly and correctly and maintain their dental and oral hygiene to avoid dental disease.